Las interpolaciones de la adaptación gráfica del Quijote por Rob Davis : herencia cervantina y modernización - Aude Plozner Bruder (E-Spania)
This article analyzes the practice of interpolation in the graphic novel of Cervantes’s Quixote adapted by Rob Davis. The aim is to determine how the adapter got to grips with the stories within the story and how he inserts them in the main plot. By a study of the tools that the illustrator has at his disposal (the layout, the colour, the drawing and writing styles), we will see how much he takes part of the debate about intercalation and how he manages to respect the Cervantine text while modernizing it.